Structural and functional characterization of myotoxin I, a Lys49 phospholipase A(2) homologue from Bothrops moojeni (Caissaca) snake venom - Soares, A. M.; Andriao-Escarso, S. H.; Angulo, Y.; Lomonte, B.; Gutierrez, J. M.; Marangoni, S.; Toyama, M. H.; Arni, R. K.; Giglio, JR (Academic Press Inc., 2000)
Myotoxin-I (MjTX-I) was purified to homogeneity from the venom of Bothrops moojeni by ion-exchange chromatography on CM-Sepharose. Its molecular weight, estimated by SDS-PAGE, was 13,400 (reduced) or 26,000 (unreduced). The extinction coefficient (E-1.0 cm(1.0 mg/ml)) of MjTX-I was 1.145 at lambda = 278 nm, pH 7.0, and its isoelectric point was 8.2 at ionic strength mu = 0.1. When lyophilized and stored at 4 degrees C, dimeric, trimeric, and pentameric forms of the protein were identified by SDS-PAGE. This heterogeneous sample could be separated into three fractions by gel filtration on Sephadex 6-50. The fractions were analyzed by isoelectric focusing, immunoelectrophoresis, and amino acid composition, which indicated that heterogeneity was the result of different levels of self-association. Protein sequencing indicated that MjTX-I is a Lys49 myotoxin and consists of 121 amino acids (M-r = 13,669), containing a high proportion of basic and hydrophobic residues. It shares a high degree of sequence identity with other Lys49 PLA(2)-like myotoxins, but shows a significantly lower identity with catalytically active Asp49 PLA(2)s. The three-dimensional structure of MjTX-I was modeled based on the crystal structures of three highly homologous Lys49 PLA(2)-like myotoxins. This model showed that the amino acid substitutions are conservative, and mainly the beta-wing region, and the C-terminal extended random coil. MjTX-I displays local myotoxic and edema-inducing activities in mice, and is lethal by intraperitoneal injection, with an LD50 value of 8.5 +/- 0.8 mg/kg, In addition, it is cytotoxic to myoblasts/ myotubes in culture, and disrupts negatively charged liposomes. In comparison with the freshly prepared dimeric sample, the more aggregated forms showed significantly reduced myotoxic activity. However, the edema-inducing activity of MjTX-I was independent of molecular association. Phospholipase A(2) activity on egg yolk, as well as anticoagulant activity, were undetectable both in the native and in the more associated forms. His, Tyr, and Trp residues of the toxin were chemically modified by specific reagents. Although the myotoxic and lethal activities of the modified toxins were reduced by these treatments, neither its edema-inducing or Liposome-disrupting activities were significantly altered. Rabbit antibodies to native MjTX-I cross-reacted with the chemically modified forms, and both the native and modified MjTX-I preparations were recognized by antibodies against the C-terminal region 115-129 of myotoxin II from B. asper, a highly Lys49 PLA(2)-homologue with high sequencial similarity. (C) 2000 Academic Press.
Keywords: Bothrops moojeni; myotoxin-I; molecular association; primary structure; molecular modeling; chemical modification